2005
DOI: 10.1111/j.1365-2842.2005.01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of defect configuration, size, and remaining teeth on masticatory function in post‐maxillectomy patients

Abstract: The aim of this study was to investigate the correlation between the masticatory function and the maxillary defect configuration, size, and remaining teeth in post-maxillectomy patients restored with an obturator prosthesis. Fifty consecutive post-maxillectomy patients (mean age 67.0) participated in this study. The subjects consisted of 26 dentate and 24 edentulous patients. Data were collected from the patients' clinical records, diagnostic casts, and a questionnaire on masticatory function to evaluate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 24 publications
4
49
1
9
Order By: Relevance
“…O desenvolvimento de forças de alavanca e linhas de fulcro aumenta drasticamente as forças sobre os tecidos de suporte durante a mastigação 16,23 . O efeito do peso intrínseco da prótese obturadora maxilar sobre os tecidos de suporte representa um fator agravante 25 , o que torna fundamental a adequada avaliação dos tecidos remanescentes para o bom desempenho da prótese e preservação das estruturas anatômicas de retenção e suporte 26 .…”
Section: Figura 3 Comparação Entre Os Grupos Experimentais Ao Longo unclassified
“…O desenvolvimento de forças de alavanca e linhas de fulcro aumenta drasticamente as forças sobre os tecidos de suporte durante a mastigação 16,23 . O efeito do peso intrínseco da prótese obturadora maxilar sobre os tecidos de suporte representa um fator agravante 25 , o que torna fundamental a adequada avaliação dos tecidos remanescentes para o bom desempenho da prótese e preservação das estruturas anatômicas de retenção e suporte 26 .…”
Section: Figura 3 Comparação Entre Os Grupos Experimentais Ao Longo unclassified
“…RPDs are especially indicated in patients with tissue deficiency, several fistulae, soft palate dysfunction, or uncoordinated nasopharyngeal sphincter action, which can lead to hyper nasal speech (8) . Furthermore, it is suggested that a prosthesis may improve the psychological status of patients as well as their quality of life (9) . Providing maxillofacial prosthetic treatment for patients with congenital and craniofacial defects should not only address physical and functional deficiencies, but, ideally, should also consider the possible psychological effects of these deformities.…”
Section: Introduction:-mentioning
confidence: 99%
“…Em geral, essas seqüelas anatômicas acarretam distúrbios funcionais, estéticos, e psicológicos (Desjardin, 1977;Birnbach;Herman, 1987;Wedel et al, 1994;Rogers et al, 2003;Koyama et al, 2005;Arigbede et al, 2006;Matsuyama et al, 2006;Know, 2006;Eckardt et al, 2007). Devido a essa grande quantidade de sequelas presentes ao tratamento do câncer bucal, a atuação de cirurgiões dentistas inserida em equipe multiprofissional, torna-se cada vez mais fundamental e expressiva para o sucesso na reabilitação do paciente.…”
Section: Discussionunclassified
“…A recuperação das funções de fala, mastigação, deglutição e estética são extremamente satisfatórios para a maioria dos pacientes usuários de próteses obturadoras (Kornblith et al, 1996;Rogers et al, 2003;Arigbede et al, 2006;Eckardt et al, 2007;Irish et al, 2009;Depprich et al, 2011;Kwon et al, 2011 (Birnbach;Herman, 1987;Black, 1992;Keyf, 2001;Rogers et al, 2003;Miracca et al 2004;Koyama et al, 2005;Kwon, 2006;Eckardt et al, 2007;Irish et al 2009;Depprich et al, 2011;Kwon et al, 2011;Miyashita et al, 2011;Miyashita et al, 2012).…”
Section: Discussionunclassified
See 1 more Smart Citation